1989
DOI: 10.1111/j.1360-0443.1989.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among DUI Offender Characteristics and Traditional Intervention Modalities: a long‐term recidivism follow‐up

Abstract: Using long-term DUI (Driving Under the Influence of Alcohol) arrest recidivism data from a controlled study of DUI intervention effectiveness, interactions among DUI interventions, age, race, education, and alcohol severity were estimated using logit analysis. Data were collected in a 9-year follow-up study of the Mississippi DUI Probation Project. The effects of short-term interventions (alcohol education schools for low alcohol severity offenders and structured group interventions for high alcohol severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Previous studies have drawn similar conclusions, arguing that the integration of treatment into the criminal justice system makes treatment accessible to individuals who might not otherwise receive it (Knight & Farabee, 2004) and that intervening while offenders are involved in the criminal justice system can also result in fewer problems with treatment compliance (Leukefeld, Staton, Webster, & Smiley McDonald, 2005). Although past research has questioned the effectiveness of court-mandated treatment (Kownacki & Shadish, 1999; Peck et al, 1985; Wells-Parker, 1989), studies have argued that identifying and treating offenders’ substance abuse and other underlying problems early in the criminal justice system process, including the use of court-mandated treatment, can potentially reduce recidivism rates (Robertson, Gardner, Xu, & Costello, 2009; Taxman, Cropsey, Young, & Wexler, 2007; Webster et al, 2009a). In this study, evidence of repeat offenders’ increased involvement in the criminal justice system underscores the importance of addressing offenders’ substance use and mental health treatment needs while under court supervision, particularly in rural areas where treatment options are often limited or absent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have drawn similar conclusions, arguing that the integration of treatment into the criminal justice system makes treatment accessible to individuals who might not otherwise receive it (Knight & Farabee, 2004) and that intervening while offenders are involved in the criminal justice system can also result in fewer problems with treatment compliance (Leukefeld, Staton, Webster, & Smiley McDonald, 2005). Although past research has questioned the effectiveness of court-mandated treatment (Kownacki & Shadish, 1999; Peck et al, 1985; Wells-Parker, 1989), studies have argued that identifying and treating offenders’ substance abuse and other underlying problems early in the criminal justice system process, including the use of court-mandated treatment, can potentially reduce recidivism rates (Robertson, Gardner, Xu, & Costello, 2009; Taxman, Cropsey, Young, & Wexler, 2007; Webster et al, 2009a). In this study, evidence of repeat offenders’ increased involvement in the criminal justice system underscores the importance of addressing offenders’ substance use and mental health treatment needs while under court supervision, particularly in rural areas where treatment options are often limited or absent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research has found an association between ethnicity, reoffending, and type of re-offence (McGovern et al, 2009;Wells-Parker et al, 1989). A recent study by Case (2008) found that non-white offenders were more likely to be re-arrested and reconvicted than white offenders.…”
Section: Risk Factors For Recidivismmentioning
confidence: 96%
“…Comparisons of offenders referred to MASEP are made, controlling for demographics and for prior drinking-and-driving behavior. Demographics are included in analyses because DUI offender status is associated with gender, age, and ethnicity (Wells-Parker et al, 1989;Caetano and McGrath, 2005;Cavaiola et al, 2007). Prior impaired driving arrests are also included in analyses because offenders with more than one DUI are more likely to recidivate than first-time offenders (Yu, 2000;Cavaiola et al, 2007).…”
Section: Mississippi Alcohol Safety Education Program (Masep)mentioning
confidence: 99%